Effect of Salinity on Growth and Vitamin C Content of Aloe Vera (Aloe vera L.) - Uswatunnisa Uswatunnisa; Wardiah Wardiah; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Study about "Effect of Salinity on Growth and Vitamin C Content of Aloe (Aloe vera L.) on August-September 2016 in Garden of Agriculture Faculty and Biology Laboratory of Educational Faculty, Syiah Kuala University. The aim of the study is to determine the effect of salinity on growth and Vitamin C content of aloe vera. Study used a Completely Randomized Design (CRD) with the provision of NaCl treatment with different concentrations are: P0 = 0 mM, 150 mM = P1, P2 = 200 mM, 250 mM P3. Parameters that were measured are plant height, leaf number, leaf length, leaf thickness and content of vitamin C in the stem of aloe vera. Data were analyzed by analysis of variance (ANOVA). Further test used in plant height, leaf length and leaf thickness was LSD (Least Significance Difference ) and a further test used in the amount of leaves and content of vitamin C are a test of Duncan. The results showed that there is a real effect (F-count ≥ F 0.05) on the growth of aloe vera on the parameters plant height, leaf number, leaf length, leaf thickness and content of vitamin C. It is concluded that treatment of different salinity give negatively effect for growth, but positively effect on vitamin C content.Keywords: Growth, salinity, Vitamin C, Aloe vera L.